Stereoselection in radical cyclization of beta-alkoxyvinyl sulfoxides: Synthesis of tetrahydrofuranyl allyl carbinols - Keum, GC; Kang, SB; Kim, Y; Lee, E (AMER CHEMICAL SOC, 2004)
Tetrahydrofuranyl allyl carbinols may be prepared stereoselectively via radical cyclization of beta-alkoxyvinyl sulfoxides, Pummerer rearrangement, and reaction with allylstannane.